Proses Perencanaan, Implementasi dan Hasil Program Perubahan Perilaku Komunitas Ibu Dalam Pemberian Makanan Sehat dan Bervariasi Bagi Anak : (Studi Penelitian Tindakan Terhadap 10 Ibu Yang Berasal Dari Keluarga Miskin Di Kelurahan Semper Barat, Jakarta Utara - Hati, Getar; Adi, Isbandi Rukminto (Jurnal Ilmu Kesejahteraan Sosial, 2016)
This article discusses about the process of community development included in planning, program implementation, and evaluation of behavior change program in women community in child feeding. The application of these processes were based on the result of community problems, needs, and capitals through participatory planning. It mapped on quality of life assessment scheme which related on malnourished children of 6-24 months old in urban poor families. This research conducted by action research method which based on analysis result of look 1 phase. This article discusses about think, act, and look 2 phases. Think phase describes planning process included formulating the aim, strategy, and intervention program. Act phase describes the implementation of social marketing program. Look 2 phase describes the results of community behavior change in 3 (three) behavior variations, i.e. continued adoption, process of adoption, and continued rejection related to the supporting and inhibiting factors within them.